Prioritised challenges in the management of acute knee dislocations are stiffness, obesity, treatment delays and associated limb-threatening injuries: a global consensus study. Issue 4 (5th March 2021) - Held, Michael; Schenck, Robert C; Khanduja, Vikas; Campos, Túlio Vinícius de Oliveira; Tapasvi, Sachin; Williams, Andy; Yau, Wai Pan; Harner, Christopher
Abstract : Objectives: Heterogeneous patient factors and injury mechanisms result in a great variety of injury patterns encountered in knee dislocations (KD). Attempts to improve outcome can focus on a wide range of challenges. The aim of this study was to establish and prioritise a list of challenges encountered when treating patients with acute KD. Methods: A modified Delphi consensus study was conducted with international knee specialists who generated a prioritised list of challenges. Selected priorities were limited to half of the possible items. Agreement of more than 70% was defined as consensus on each of these items a priori. Results: Ninety-one international surgeons participated in the first round. The majority worked in public hospitals and treated patients from low-income and middle-income households. Their propositions were prioritised by 27 knee surgeons from Europe, Africa, Asia, as well as North and South America, with a mean of 15.3 years of experience in knee surgery (SD 17.8). Consensus was reached for postoperative stiffness, obesity, delay to presentation and associated common peroneal nerve injuries. Challenges such as vascular injuries, ipsilateral fractures, open injuries as well as residual laxity were also rated high. Most of these topics with high priority are key during the initial management of a patient with KD, at presentation. Topics with lower priority were postsurgical challenges, such as patient insight, expectations and compliance, rehabilitation programme, and pain management. Conclusion: This consensus study has a wide geographical footprint of experts around the world practising in various settings. These participants prioritised stiffness, obesity, treatment delays and associated limb-threatening injuries as the most important challenges when managing a patient with acute KD. This list calls for applicable and feasible solutions for these challenges in a global setting. It should be used to prioritise research efforts and discuss treatment guidelines. Level of evidence: V.